An introduction to Geoinformatics - Srivastava, G. S. (McGraw-Hill's AccessEngineering., 2014)
"Geoinformatics is the integration of different disciplines dealing with spatial information. The advent of Satellite Remote Sensing and subsequent development of Global Positioning System (GPS) and Geographical Information System (GIS) have made significant changes in surveying and map making. In light of this, both in the academia and the industry, these topics have been brought together under one umbrella term-Geoinformatics. This is the first comprehensive study on Geoinformatics meant for students and professionals which brings together the essential elements of Photogrammetry, Remote Sensing, GPS and GIS. A basic understanding of these components is crucial for carrying out various types of surveys, navigation, geodynamics, hydrology, disaster management, etc.".